2022
DOI: 10.1111/jam.15432
|View full text |Cite
|
Sign up to set email alerts
|

The sustainable mitigation of in vitro ruminal biogas emissions by ensiling date palm leaves and rice straw with lactic acid bacteria and Pleurotus ostreatus for cleaner livestock production

Abstract: Aims:The sustainable utilization of date palm leaves (DPL) and rice straw (RS) as feed materials for ruminant was evaluated using an in vitro wireless gas production (GP) technique. Methods and Results: DPL and RS were individually ensiled with lactic acid bacteria (LAB) for 45 days or used as substrates for the cultivation of Pleurotus ostreatus (PO) mushroom for 35 days. A total mixed ration was formulated as a control ration.In the other rations, berseem hay replaced DPL (ensiled without additives or ensile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Date palm (Phoenix dactilifera) leaves (DPL) are an example of the agricultural byproducts with a considerable potential nutritive value, but unsatisfactory use [2]. The nutritive value of DPL is hindered due to high concentration of fiber [3]. With about 20 kg of leaves produced from each tree, 14 million date palm trees generate approximately 650,000 tons of dry matter (DM) annually in Egypt [4].…”
Section: Introductionmentioning
confidence: 99%
“…Date palm (Phoenix dactilifera) leaves (DPL) are an example of the agricultural byproducts with a considerable potential nutritive value, but unsatisfactory use [2]. The nutritive value of DPL is hindered due to high concentration of fiber [3]. With about 20 kg of leaves produced from each tree, 14 million date palm trees generate approximately 650,000 tons of dry matter (DM) annually in Egypt [4].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has also confirmed that LAB inoculants in corn silage can improve the total VFA concentration in the rumen (Monteiro et al, 2021 ), compared with the control group, the increase was 13.7%. Kholif et al ( 2021 ) also reported that the addition of LAB to date palm leaves could increase the total VFA in the rumen. Similar studies were reported in wheat straw silage that the additive LAB can improve the acetic acid and total VFA concentration of wheat straw silage (Babaeinasab et al, 2015 ).…”
Section: Discussionmentioning
confidence: 97%
“…Zhang Q. et al ( 2016 ) documented that the addition of LAB reduced the ADF and NDF contents in L. chinensis silage. The pH value is one of the key indexes to measure the quality of fermentation during silage fermentation (Kholif et al, 2021 ). The low pH value during silage fermentation means that the activity of harmful microorganisms was inhibited and reduced the loss of nutrients (Fan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Egypt, approximately 650,000 tons of leaves’ dry matter (DM) is produced annually from about 14 million trees [ 3 , 4 ]. DPL are not properly utilized due to high fiber (43–73% neutral detergent fiber (NDF) [ 5 ]) and low crude protein (CP) (4.2 to 16.5% of DM [ 6 , 7 ]) contents and low nutritive value and digestibility. Ensiling low-quality forages with silage additives is common to improve their fermentation profile and nutritive value and to reduce adverse bacterial growth and negative effects of some antinutritional factors in feeds [ 8 ].…”
Section: Introductionmentioning
confidence: 99%